9.1k views
5 votes
How to solve -2(v-2)=-3-2v i need it step by step

User Padagomez
by
6.1k points

2 Answers

3 votes

Answer:O0

Explanation:

2*(v-2)-(-3-2*v)=0

STEP

1

:

Equation at the end of step 1

(0 - 2 • (v - 2)) - (-2v - 3) = 0

STEP

2

:

Equation at the end of step 2

7 = 0

STEP

3

:

Equations which are never true:

3.1 Solve : 7 = 0

User Olokki
by
6.1k points
0 votes

Answer:

No solution

Explanation:

Given: -2(v-2)=-3-2v

Distribute -2 at the left side of the equal sign:

-2v+4=-3-2v

Put all like terms in one side:

-2v+2v=-3-4

Combine all like terms:

0=-12

Answer: No solution

User EagleBeak
by
6.0k points